Efek Ekstrak Buah Etlingera hemisphaerica terhadap Penurunan Kadar Gula Darah Mus Musculus Swiss Webster Jantan - Endang Suswati; Nugroho Aji Waluyo; Rama Saputra; Zico Fakhrur Rozi (Jurnal Biosilampari : Jurnal Biologi, 2025)
Diabetes mellitus is a chronic metabolic disorder characterized by hyperglycemia due to impaired insulin secretion or action. This study aimed to evaluate the effect of Etlingera hemisphaerica fruit extract on reducing blood glucose levels in male Swiss Webster Mus musculus induced with 10% sugar solution. This experimental research employed a completely randomized design. A total of 25 male Mus musculus were divided into five groups: a negative control group (no treatment) and four treatment groups receiving Etlingera hemisphaerica fruit extract at doses of 0.13 mg/kgBW, 0.26 mg/kgBW, 0.38 mg/kgBW, and Glibenclamide. Blood glucose levels were measured using a glucometer before and after 17 days of treatment. The results showed that the administration of Etlingera hemisphaerica fruit extract significantly reduced blood glucose levels in the treatment groups compared to the positive control group (p<0.05). The dose of 0.13 mg/kgBW exhibited the most optimal blood glucose-lowering effect. This hypoglycemic effect is associated with the flavonoid content in the fruit extract, which enhances insulin sensitivity and reduces oxidative stress.